2020
DOI: 10.3389/fphar.2020.582348
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Triple Combination Therapy With Lopinavir-Ritonavir, Azithromycin, and Hydroxychloroquine on QT Interval and Arrhythmic Risk in Hospitalized COVID-19 Patients

Abstract: Introduction No data are provided about the effect of triple combination therapy with Lopinavir/Ritonavir (LPN/RTN), hydroxychloroquine (HQ) and azithromycin (AZT) on corrected QT (QTc) interval and arrhythmic risk, in COVID-19 patients. This study aims to describe the incidence of extreme QTc interval prolongation among COVID-19 patients on this experimental treatment and to identify the clinical features associated with extreme QTc prolongation. Materials and Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 22 publications
(29 reference statements)
1
24
0
Order By: Relevance
“…In Bessiere et al study, combination therapy with hydroxychloroquine and azithromycin caused prolonged Q-T in 10.7-36% of patients [23]. Russo et al study showed that 23% of patients reached developed arrhythmias following the treatment of COVID-19 with hydroxychloroquine and azithromycin [24]. The results of Moyle G et al study, revealed a meaningful decrease in unconjugated and total bilirubin following zinc sulfate (ZnSO4) intake and a limited decrease in ATV/r plasma exposure.…”
Section: Discussionmentioning
confidence: 97%
“…In Bessiere et al study, combination therapy with hydroxychloroquine and azithromycin caused prolonged Q-T in 10.7-36% of patients [23]. Russo et al study showed that 23% of patients reached developed arrhythmias following the treatment of COVID-19 with hydroxychloroquine and azithromycin [24]. The results of Moyle G et al study, revealed a meaningful decrease in unconjugated and total bilirubin following zinc sulfate (ZnSO4) intake and a limited decrease in ATV/r plasma exposure.…”
Section: Discussionmentioning
confidence: 97%
“…Previous articles have notified a clinically significant DDI among hydroxychloroquine, azithromycin, and ritonavir in patients with COVID-19 pneumonia that led to prolonged QT interval. 10,28 Drug Interactions Checker reports reveal a potential weak interaction between hydroxychloroquine and DRV/c and no interaction with azithromycin, but coadmin-istration has not been studied and it is not known if the interaction is clinically relevant. DRV/c could potentially increase hydroxychloroquine exposure by inhibition of P450 enzymes, but dose adjustment is not recommended.…”
Section: Discussionmentioning
confidence: 99%
“…According to these findings, routine testing of clotting factors should be integrated with current triage strategies for patients with suspected COVID-19 [ 20 ] in order to collect more detailed information for their clinical management. The potential association between antithrombotic therapy and the clinical presentation of COVID-19 is still debated [ 21 ], and further studies are necessary to evaluate the possible role of clotting factors, in particular fibrinogen, in guiding the use of antiviral and antithrombotic therapies [ 22 , 23 , 24 ] as part of routine medical therapy during hospitalization.…”
Section: Discussionmentioning
confidence: 99%